1
$\begingroup$

Find where m is an integer: $$S = 1+\sum_{n=1}^{\infty}\frac{n!}{(mn)!}$$

When we rewrite this sum as one plus a function of $x$ and multiply the $n^{th}$ term of the series by $x^{mn-1}$, the resulting function solves for the differential equation $$\frac{d^{m-1}f(x)}{dx^{m-1}} = \frac1m + \frac1{xf(x)}$$ and hence we can replace $f(x)$ with $s(x)$ and set $s(0) = 1$. Then use that to find $s(1)$ which is $S$.

I'm looking for an alternative method because I'm having trouble dealing with this differential equation.

$\endgroup$
  • 2
    $\begingroup$ There's no nice closed form. Per Mathematica, when $m=4$, we obtain 1/24 HypergeometricPFQ[{1}, {5/4, 3/2, 7/4}, 1/256] which Mathematica doesn't know how to simplify. $\endgroup$ – Patrick Stevens Sep 5 '17 at 8:36
1
$\begingroup$

Using integrals, one gets (based on Prove the following series $\sum\limits_{s=0}^\infty \frac{1}{(sn)!}$):

$\displaystyle S_m = \sum\limits_{n=0}^\infty \frac{n!}{(mn)!} = \sum\limits_{n=0}^\infty \frac{1}{(mn)!} \int\limits_0^\infty \frac{x^n}{e^x} dx =\int\limits_0^\infty \frac{1}{e^x} \left( \sum\limits_{n=0}^\infty \frac{x^n}{(mn)!}\right) dx$

$\hspace{7mm} \displaystyle = \frac{1}{m} \int\limits_0^\infty \left(\sum\limits_{r=0}^{m-1} e^{\sqrt[m]{x}e^{i2\pi r/m} -x}\right) dx = \frac{1}{m} \sum\limits_{r=0}^{m-1} \int\limits_0^\infty e^{\sqrt[m]{x}e^{i2\pi r/m} -x} dx $

$\endgroup$
2
$\begingroup$

Considering $$S_m = \sum_{n=1}^{\infty}\frac{n!}{(mn)!}$$ beside the case $m=2$ for which $$S_2=\frac{1}{2} \sqrt[4]{e} \sqrt{\pi } \text{erf}\left(\frac{1}{2}\right)$$ as Patrick Stevens commented, we are left with hypergeometric functions which apparently do not simplify at all.

They show quite nice patterns $$S_3=\frac{1}{3!} \, _1F_2\left(1;\frac{4}{3},\frac{5}{3};\frac{1}{3 ^3}\right)$$ $$S_4=\frac{1}{4!} \, _1F_3\left(1;\frac{5}{4},\frac{6}{4},\frac{7}{4};\frac{1}{4^4}\right)$$ $$S_5=\frac{1}{5!} \, _1F_4\left(1;\frac{6}{5},\frac{7}{5},\frac{8}{5},\frac{9}{5};\frac{1}{5^5}\right)$$ $$S_6=\frac{1}{6!} \, _1F_5\left(1;\frac{7}{6},\frac{8}{6},\frac{9}{6},\frac{10}{6},\frac{11}{6};\frac{ 1}{6^6}\right)$$ $$S_7=\frac{1}{7!}\, _1F_6\left(1;\frac{8}{7},\frac{9}{7},\frac{10}{7},\frac{11}{7},\frac{12}{7},\frac{13}{7};\frac{1}{7^7}\right)$$

In fact, it seems that the asymptotics is just $S_m\sim\frac{1}{m!}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.